Electromyographical Gait Characteristics in Parkinson’s Disease: Effects of Combined Physical Therapy and Rhythmic Auditory Stimulation - Bailey, Christopher A.; Corona, Federica; Murgia, Mauro; Pili, Roberta; Pau, Massimiliano; Côté, Julie N. (Frontiers in Neurology, 2018)
Background: In persons with Parkinson’s disease (PD), gait dysfunctions are often associated to abnormal neuromuscular function. Physical therapy combined with auditory stimulation has been recently shown to improve motor function and gait kinematic patterns; however, the underlying neuromuscular control patterns leading to this improvement have never been identified. Objectives: 1) Assess the relationships between motor dysfunction and lower limb muscle activity during gait in persons with PD; 2) Quantify the effects of physical therapy with rhythmic auditory stimulation (PT-RAS) on lower-limb muscle activity during gait in persons with PD. Methods: Participants (15 with PD) completed a 17-week intervention of PT-RAS. Gait was analyzed at baseline, after 5 weeks of supervised treatment (T5), and at a 12-week follow-up (T17). For each session, motor dysfunction was scored using the United Parkinson Disease Rating Scale, and muscle activation amplitude, modulation, variability, and asymmetry were measured for the rectus femoris, tibialis anterior, and gastrocnemius lateralis (GL). Spearman correlation analyses assessed the relationships between dysfunction and muscle activity, and mixed effect models (session x muscle) tested for intervention effects. Results: PT-RAS was effective in decreasing motor dysfunction by an average of 23% (T5) to 36% (T17). Higher GL activity variability and bilateral asymmetry were correlated to higher dysfunction (ρ = .301 - .610, ps < .05) and asymmetry significantly decreased during the intervention (p < .05). Conclusions: Results suggest that gait motor dysfunction in PD may be explained by neuromuscular control impairments of GL that go beyond simple muscle amplitude change. Physical therapy with rhythmic auditory stimulation improves bilateral symmetry, but its effect on muscle variability requires future investigation.